2013
DOI: 10.1186/1743-422x-10-299
|View full text |Cite
|
Sign up to set email alerts
|

Role of viral and host factors in interferon based therapy of hepatitis C virus infection

Abstract: The current standard of care (SOC) for hepatitis C virus (HCV) infection is the combination of pegylated interferon (PEG-IFN), Ribavirin and protease inhibitor for HCV genotype 1. Nevertheless, this treatment is successful only in 70-80% of the patients. In addition, the treatment is not economical and is of immense physical burden for the subject. It has been established now, that virus-host interactions play a significant role in determining treatment outcomes. Therefore identifying biological markers that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 147 publications
(151 reference statements)
2
15
0
Order By: Relevance
“…Our study showed the HCV sub‐genotype 3a as the most prevalent HCV genotype (56.4%; n = 79/140) with the highest response to interferon‐based therapy (91%; n = 72/79). These results are in concordance with the previous studies .…”
Section: Discussionsupporting
confidence: 94%
“…Our study showed the HCV sub‐genotype 3a as the most prevalent HCV genotype (56.4%; n = 79/140) with the highest response to interferon‐based therapy (91%; n = 72/79). These results are in concordance with the previous studies .…”
Section: Discussionsupporting
confidence: 94%
“…We excluded 581 studies based on review of the titles and abstracts. We excluded another seven studies20212223242526 because they were not case-control studies, three studies because they did not report genotypes272829, and eight studies3031323334353637 because they did not involve patients with HCC. A further two studies3839 were excluded because they included either patients with only liver cirrhosis or an aggregated patient population with HCC or liver cirrhosis.…”
Section: Resultsmentioning
confidence: 99%
“…According to worldwide study, more than two hundred million people are infected by HCV 2. HCV is single-stranded (ss) RNA enveloped virus, which is being placed in family flaviviridae 3.…”
Section: Introductionmentioning
confidence: 99%